Between the lines: The Star and Sowetan and the construction of national identity in the new South Africa - Epstein, Richard Laurence (My University, 2015)
This thesis examines, through an interpretative framework of specificity and difference, how the ‘New South Africa’ is being constructed by The Star and Sowetan newspapers. Using semiotics as the method of analysis, it gives detailed deconstructive readings of The Star and Sowetan's coverage of the inauguration of Nelson Mandela as South Africa's first post-apartheid head of state. In the process it reveals how signs are mobilised to give a particular meaning to the New South Africa. The findings of this study show that there is no single construction of the New South Africa. Instead, there are different, although not necessarily intentional, constructions which are specific and relative in nature. They privilege specific forms of identity which are not applicable to everyone who claims to be South African. This leads to the conclusion that we cannot view nationalisms and national identities as being coherent and unified. Rather, it concludes that we should see them as being constituted by specificity and difference.